2020
DOI: 10.1029/2020tc006065
|View full text |Cite
|
Sign up to set email alerts
|

The Cenozoic Evolution of Crustal Shortening and Left‐Lateral Shear in the Central East Kunlun Shan: Implications for the Uplift History of the Tibetan Plateau

Abstract: The timing of crustal shortening and strike-slip faulting along the East Kunlun Shan provides insight into the history of surface uplift and may constrain the time at which the Tibetan Plateau reached high elevations. We investigate a series of extensional basins and restraining bends along the Xidatan strand of the Kunlun strike-slip fault, which provide an ideal setting to unravel the tectonic history of the northern plateau margin. We present new apatite (U-Th)/He, apatite fission track, and zircon (U-Th)/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 144 publications
(233 reference statements)
1
22
0
Order By: Relevance
“…Previous studies emphasize the Paleocene to Eocene rapid exhumation in the EKLS and argue for an early Cenozoic shortening event in the northern Tibetan Plateau (Clark et al, 2010;Staisch et al, 2020;Tian et al, 2020;Wang et al, 2016aWang et al, , 2017aYuan et al, 2006). However, reanalysis of existing low-temperature thermochronologic data and sedimentary records provides an alternative scenario.…”
Section: Late Oligocene Tectonic Uplift Of the Eklsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies emphasize the Paleocene to Eocene rapid exhumation in the EKLS and argue for an early Cenozoic shortening event in the northern Tibetan Plateau (Clark et al, 2010;Staisch et al, 2020;Tian et al, 2020;Wang et al, 2016aWang et al, , 2017aYuan et al, 2006). However, reanalysis of existing low-temperature thermochronologic data and sedimentary records provides an alternative scenario.…”
Section: Late Oligocene Tectonic Uplift Of the Eklsmentioning
confidence: 99%
“…(2013); (6) Staisch et al. (2020); (7) Tian et al. (2020); (8) Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…13-8 Ma. Third, the intensification of precipitation (Nie et al, 2017) Staisch et al (2020). "Debated events" represents the evidence for Cenozoic deformation in the Qilian Shan, which are highly debated.…”
Section: Qilian Shan During the Middlelate Miocenementioning
confidence: 99%
“…Fine fraction (<75 μm) of modern river sediments originating from the East Kunlun Shan yield ε Nd values between −9.9 and −7.9 (Figure 1b; Wu et al., 2010), which may be controlled by widespread early Paleozoic and Permo‐Triassic granites with ε Nd values ranging from −9.2 to 3.6 (Mo et al., 2007). Studies along the East Kunlun Shan suggest the Eocene to late Oligocene thrust faulting (Clark et al., 2010; Li, Zheng, et al., 2020; Wang, Feng, et al., 2016; Wang, Shi, et al., 2017; Yin et al., 2007), followed by an early Miocene left‐lateral shear along the Kunlun Fault (Duvall et al., 2013; Staisch et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The process of desert formation in Northern China was once understood to be a result of sustained orogenesis of the Qinghai-Tibetan Plateau and surrounding areas during the Quaternary (Meng & Zhang, 2011;Wu, 2002). However, new data showed that the plateau reached its height earlier than originally thought in the Miocene (Hu et al, 2020;Staisch et al, 2020) and suggested that the deserts might have originated during glacial periods, when global ice volume was high and, thus, liquid water was more limited (Sun et al, 2018). The same climatic processes that gave rise to the deserts also appear to have profoundly shaped regional plant diversity and yielded highly complex demographic histories of native species (Ge et al, 2005).…”
Section: Introductionmentioning
confidence: 96%